JANJI DAN SUMPAH: KAJIAN TEMATIK TAFSIR AL-MUNIR Q.S. AN-NAHL: 91 KARYA WAHBAH AZ-ZUHAILI - Husna, Nihayatul (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2022)
Promises or oaths are two different things but both must be kept because there is a mandate in both. The use of these terms has very different meanings and positions, especially in the Qur'an. Promises and oaths if violated have the potential to harm the promised party to the loss of trust in the perpetrators. Departing from this, it is important to know what promises and oaths are in the Qur'an and what is their position for violators of promises and oaths in the view of the commentators. In this paper, the researcher focuses on Wahbah Zuhaili's perspective on the interpretation of the Qur'an Surah an-Nahl/16: 91 in his commentary entitled Al-Munir fi al-Aqidah wa al-Syari'ah wa al-Manhaj. This type of research conducted by the author is qualitative research. The data collection technique uses library research (library research) in which the author answers the existing problems by referring to several commentary books, articles, and journals related to the title. The source of the data taken comes from primary data, namely the book of Al-Munir's commentary and secondary data from literature relevant to the title above. The method used in this research is thematic method, with a descriptive analysis approach. The results of this study indicate that the word promise refers to the word "Al-Aiman", and the word oath refers to the word "Al-qasam" or "Al-'Ahd". Meanwhile, according to Wahbah Zuhaili, those who break an oath or promise are included in the class of hypocrites.